Search for the Decay of the Higgs Boson to Charm Quarks with the ATLAS Experiment - Onofre, A. (2018)
A direct search for the standard model Higgs boson decaying to a pair of charm quarks is presented. Associated production of the Higgs and Z bosons, in the decay mode ZH→ℓ+ℓ−c¯c is studied. A data set with an integrated luminosity of 36.1  fb−1 of pp collisions at √s=13TeV recorded by the ATLAS experiment at the LHC is used. The H→c¯c signature is identified using charm-tagging algorithms. The observed (expected) upper limit on σ(pp→ZH)×B(H→c¯c) is 2.7 (3.9+2.1−1.1) pb at the 95% confidence level for a Higgs boson mass of 125 GeV, while the standard model value is 26 fb.